“PENUH ROH KUDUS” KUASA RESISTENSI: TAFSIR KPR 4: 1-22 DALAM PERSPEKTIF POSKOLONIAL SUBALTERN GAYATRI CAKRAVOTI SPIVAK - Aliyanto, Deky Nofa (LOGIA: Jurnal Teologi Pentakosta, 2024)
AbstractThe horizon of interpretation of Kpr 4: 1-22 is predominantly based on a theological perspective (Christological, soteriological and missiological) with a critical historical approach to analyzing the text of the holy book. In a society at any time and anywhere, socio-political aspects are an integral and significant part that shapes the dynamics and social structure of society. So that within the framework of religion and society, the religious mystical experience of being "full of the Holy Spirit" as recorded in Kpr 4: 1-22 is undoubtedly related to the socio-political aspects of the era. This research aims to show that postcolonial interpretation of Acts 4:1-22 provides a concrete example of how the power of socio-political resistance can be expressed through the full spiritual experience of the Holy Spirit from Subaltern groups against the hegemony and domination of religious elite groups. This research uses a postcolonial hermeneutic approach which investigates issues of authority and power in the context of colonialism at the center of the study (interpretation) of the Bible. The research results show, First: The Jerusalem Council was a form of hegemony and domination of the religious elite group through imprisonment, silencing and threats of violence against Peter and John who were identical to the subaltern class group. Second: The Holy Spirit who filled the subaltern class group (Peter and John) in the phenomenon of mystical religious experience gave them the power to provide resistance so that the hegemony and domination of the religious elite group collapsed. Key words: Full of the Holy Spirit, Kpr 4:1-22, Resistance, postcolonial, Subaltern, hegemony, domination.